DIFUSI INOVASI PEMBELAJARAN AQIDAH AKHLAK DI SEKOLAH DASAR - Rosfiani, Okta (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2017)
Schools today face great challenges in the world at all levels of education ranging from elementary school to high school. In addition to providing basic academic knowledge and skills, and promote the development of character, lately the school is called to play a major role in helping solve social problems among youths. Objectives to be achieved in this study: 1) describe the behavior and characteristics of students MI which has been obtained character education through learning the character of the national curriculum, 2) describe, analyze, and interpret patterns of behavior of a group of public school (in this case of students) evolve over time. This study uses a mix design method (design method mix) for surveying and ethnography. The results showed that the students' behavior and characteristics of the MI which has been obtained through the character education moral subjects showed more character MI students and in being better, also better understand the rules and norms of each student's behavior is more directed to good moral based kisah- story morals taught in the lesson than students who did not get Akhlaq subjects.